1991
DOI: 10.1002/ijc.2910480218
|View full text |Cite
|
Sign up to set email alerts
|

Sensitizer for photodynamic therapy of cancer: A comparison of the tissue distribution of photofrin ii and aluminum phthalocyanine tetrasulfonate in nude mice bearing a human malignant tumor

Abstract: The distribution of Photofrin II (P-II) and aluminum phthalocyanine tetrasulfonate (AIPCS4) in tissues of BALB/c nu/nu nude mice bearing the LOX human melanoma was measured fluorimetrically at different times after intraperitoneal injection of the drugs, 20 mg/kg body weight. The plasma levels of the drugs as well as the excretion in feces and urine were also determined. The plasma concentrations of both drugs were found to build up in a similar manner during the first 30 min after injection. Thereafter, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…ence of uptake time for Photofrin. This may be due to the fact that Photofrin is taken up more slowly [52] than the other sensitizers used in this study. In fact, for the relatively short uptake times (up to 90 min) in the present study, the uptake kinetics was rate limiting.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…ence of uptake time for Photofrin. This may be due to the fact that Photofrin is taken up more slowly [52] than the other sensitizers used in this study. In fact, for the relatively short uptake times (up to 90 min) in the present study, the uptake kinetics was rate limiting.…”
Section: Discussionmentioning
confidence: 90%
“…One distinguishes between 'fast'-and 'slow'-acting photosensitizers, having characteristic elimination half-lives (t 1/2 ) in plasma. For example, for lipophilic Photofrin t 1/2 s8 h [52], for PpIX t 1/2 s2 h [41], for hydrophilic AlPcS n t 1/2 s1.5 h [52], whereas for liposomally encapsulated BPD t 1/2 s20 min [4]. However, with topical application on the CAM, less difference is expected than with systemic administration, since uptake through the extremely thin ectoderm is dominated by diffusion, which is of the same order of magnitude for molecules having similar molecular weights.…”
Section: Choice Of Treatment Variablesmentioning
confidence: 99%
“…administration, although absolute drug concentrations were higher in some organs (liver and kidney) after i.v. administration (Bellnier et al, 1989;Peng et al, 1991). Photofrin levels in the bladder were not measured in these studies.…”
Section: Histologymentioning
confidence: 94%
“…Detectable levels of the fluorescent component of Photofrin were, however, present in the normal bladder for up to 10 days. Drug uptake and distribution studies in mice have also demonstrated a slow clearance of these sensitisers from other normal tissues (Peng et al, 1991;Bellnier et al, 1989), with detectable drug levels in muscle, skin, heart, lung, spleen, kidney and liver at 75 days after injection of 5 mg kg-' Photofrin (Bellnier et al, 1989). Several studies have also demonstrated longer elimination times for Photofrin (plasma and tissue) after i.p.…”
Section: Histologymentioning
confidence: 99%
“…Phthalocyanines are interesting, as many of them have a much stronger fluorescence than HpD, and at longer wavelengths with less overlap with the tissue autofluorescence (Spikes 1986). A better selectivity for malignant tissues has also been found (van Leengoed et al 1990, Peng et al 1991. Other PDT drugs examined for fluorescence tumour marking capabilities include chlorins (mono-aspartyl chlorin e 6 (MACE), di-aspartyl chlorin e 6 (DACE), meso-tetra hydroxyphenyl chlorin (mTHPC) and benzoporphyrin derivatives (Roberts et al 1988, Andersson-Engels et al 1993, Alian et al 1994.…”
Section: Fluorophoresmentioning
confidence: 99%